2020
DOI: 10.7554/elife.56738
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive modulation by the adhesion GPCR CIRL promotes mechanosensory signal discrimination

Abstract: Adhesion-type GPCRs (aGPCRs) participate in a vast range of physiological processes. Their frequent association with mechanosensitive functions suggests that processing of mechanical stimuli may be a common feature of this receptor family. Previously, we reported that the Drosophila aGPCR CIRL sensitizes sensory responses to gentle touch and sound by amplifying signal transduction in low-threshold mechanoreceptors (Scholz et al., 2017). Here, we show that Cirl is also expressed in high-threshold mechanical noc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 90 publications
(153 reference statements)
1
9
0
Order By: Relevance
“…Albeit low, the dark activity of bPAC(wt) 0.057 min -1 (0.0009 s -1 ) is sufficient to increase resting cAMP in the absence of light, in agreement with other reports [44,52,53]. In consequence, about 25% of Drosophila larvae display nocifensive-like bending behavior in the absence of Fig.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Albeit low, the dark activity of bPAC(wt) 0.057 min -1 (0.0009 s -1 ) is sufficient to increase resting cAMP in the absence of light, in agreement with other reports [44,52,53]. In consequence, about 25% of Drosophila larvae display nocifensive-like bending behavior in the absence of Fig.…”
Section: Discussionsupporting
confidence: 91%
“…3B), consistent with nociceptor sensitization by cAMP. Notably, the larvae also displayed spontaneous bending in the dark, likely due to the dark activity of bPAC(wt) [13,44]. This undesirable dark phenotype was removed in larvae expressing the new variants (Fig.…”
Section: Engineered Bpac Variants Only Induce Drosophila Nocifensive Behavior In the Lightmentioning
confidence: 95%
See 2 more Smart Citations
“…In addition to the enhancing effect on the low-threshold mechanosensory neurons responsible for gentle touch, sound, and proprioceptive input, Dannhäuser et al recently showed that dCirl is also expressed in high-threshold mechanical neurons that respond to strong mechanical stimuli [119]. Interestingly, however, dCirl exerts an opposite effect on the nociceptive neurons by dampening their response to mechanical stimulation.…”
Section: Adgrl1/lphn1/cirlmentioning
confidence: 99%